2017
DOI: 10.1039/c6sc03374a
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox radical conjugate addition of dithiane-2-carboxylate promoted by an iridium(iii) phenyl-tetrazole complex: a formal radical methylation of Michael acceptors

Abstract: An iridium(iii) phenyl-tetrazole complex is a versatile catalyst for a new photocatalytic Michael reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 60 publications
(35 reference statements)
0
61
0
1
Order By: Relevance
“…It should be mentioned that cyclometalated Ir(III) complexes have been previously employed to generate reactive radical species upon light irradiation. [61][62][63] Therefore, we explored the possibility of employing the luminescent additives as photopolymerization initiators, but no hardening of the resin was observed for concentrations up to 0.5 wt% and irradiation times up to 10 s. Emission spectra of 3D printed luminescent dog-bones revealed that the emissive behaviour of the complexes has been maintained after the photopolymerization (Fig. 8a).…”
Section: Phosphorescent Inksmentioning
confidence: 99%
“…It should be mentioned that cyclometalated Ir(III) complexes have been previously employed to generate reactive radical species upon light irradiation. [61][62][63] Therefore, we explored the possibility of employing the luminescent additives as photopolymerization initiators, but no hardening of the resin was observed for concentrations up to 0.5 wt% and irradiation times up to 10 s. Emission spectra of 3D printed luminescent dog-bones revealed that the emissive behaviour of the complexes has been maintained after the photopolymerization (Fig. 8a).…”
Section: Phosphorescent Inksmentioning
confidence: 99%
“…Under photoredox reaction conditions, carboxylic acids have been successfully applied as the alkyl radical equivalent for decarboxylative Michael additions . However, the generation of the methyl radical from acetic acid is still challenging for photocatalytic reactions . In general, the addition of methyl radicals, using an ambitious method based on a Minisci‐type reaction, has still not been well developed in photocatalysis .…”
Section: C‐methylationmentioning
confidence: 99%
“…devised 1,3‐dithiane‐2‐carboxylic acid ( 25 ) as the starting material to react with a readily accessible and less costly iridium photocatalyst ( 26 ) to obtain the methyl radical precursor ( 27 ) under photoredox conditions. The radical Michael conjugation leads to the dithiane‐substituted products ( 28 ), which react with Raney‐Ni to give the methylated products ( 30 ) (Scheme ) …”
Section: C‐methylationmentioning
confidence: 99%
“…Its organometallic compounds are typically very stable and can glow intense luminescence all across the Vis region through rational design of the ligand environment . Thanks to its remarkable stability in several oxidation states, it is a key chemical element in industrial catalytic processes, solar‐driven photoelectrochemistry and in the expanding area of photoredox catalysis …”
Section: Figurementioning
confidence: 99%